Control of cracking in concrete by steel reinforcement : an examination of some of the mechanisms involved - Wilson, Derek Leslie Skeeles (Department of Civil Engineering, 2016)
The techniques tried up till now to model the problem of cracking in reinforced concrete have been largely empirical. Many relationships have been identified between certain parameters and the occurrence and size of cracks. This thesis reviews these, reports on the current state of knowledge, and discusses some of the theories proposed. Because of the great variation and complexity of the materials and stress interactions involved, the problem has to date defied completely objective theoretical modelling. The finite element method provides a powerful new modelling tool for theoretical simulation of complex real problems. Recent developments on constitutive models for concrete make this method extremely attractive for use in this case. This thesis attempts to make use of these tools by carrying out some analyses of the cracking of reinforced concrete prisms stressed in tension. The method is found to be a viable way of examining mechanisms and effects which are not ordinarily visible in laboratory experiments. These mechanisms are discussed in the light of the experimental findings recorded in the literature.